24th European Conference on Optical Communication. ECOC '98 (IEEE Cat. No.98TH8398)
DOI: 10.1109/ecoc.1998.732709
|View full text |Cite
|
Sign up to set email alerts
|

Electronic equalisation of PMD and chromatic dispersion induced distortion after 100 km standard fibre at 10 Gbit/s

Abstract: Polarisation mode dispersion distortion equalisation with more then I I dB power penalty reduction is demonstrated for the first time at I O G W s after lOOkm standardfibre using electronic filtering in the receiver.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(5 citation statements)
references
References 5 publications
0
5
0
Order By: Relevance
“…The experiment shows that PMD compensation is possible at the highest bitrate that is presently used for electrical TDM transmission systems. In contrast to electronic PMD compensation [7] the optical scheme allows to compensate for larger DGD's, does not increase the noise bandwidth of the receiver, and does not impair the eye diagram like any added electronic circuit would at these high frequencies.…”
Section: B 40 Gb/s With Three-section Equalizermentioning
confidence: 99%
See 1 more Smart Citation
“…The experiment shows that PMD compensation is possible at the highest bitrate that is presently used for electrical TDM transmission systems. In contrast to electronic PMD compensation [7] the optical scheme allows to compensate for larger DGD's, does not increase the noise bandwidth of the receiver, and does not impair the eye diagram like any added electronic circuit would at these high frequencies.…”
Section: B 40 Gb/s With Three-section Equalizermentioning
confidence: 99%
“…In the latter case which this paper is about speed and insertion loss of polarization transformers, and possibly a variation of a DGD section are key issues. In the electrical part of an optical receiver, PMD can be equalized by transversal filters or quantized feedback [7]. Since the photocurrent is proportional to the squared field vector magnitude not all PMD distortions can be undone electronically, and we concentrate therefore on the optical solutions.…”
Section: Introductionmentioning
confidence: 99%
“…This tailors the pulse shape at the input of the decision circuitry, thereby improving the receiver sensitivity. Recently, experiments have shown that an 11 dB improvement could be obtained in a 10 Gb/s long haul system to compensate for the effects of polarization-mode dispersion (PMD) by using tap delay line filters [1], [2].…”
Section: Introductionmentioning
confidence: 99%
“…Together with the advances in high-speed digital signal processing (DSP) techniques, coherent detection is believed to be one of the next major enabling technologies to realize high spectral efficiency transmission at 100Gb/s per channel and beyond. The flexibility and scalability of DSP in coherent systems are studied for compensation of transmission impairments such as chromatic dispersion (CD) [2][3][4][5], polarization-mode dispersion (PMD) [6][7][8], Kerr nonlinearity [5,[9][10][11][12][13] and carrier phase recovery [14][15][16]. For DSP based CD compensation, Savory et al…”
Section: Introductionmentioning
confidence: 99%